2021
DOI: 10.1136/jmedgenet-2020-107548
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the UK Genetic Severity Score for NF2: a proposal for the addition of a functional genetic component

Abstract: BackgroundNeurofibromatosis type 2 (NF2) is an autosomal dominant disorder characterised by the development of multiple schwannomas, especially on vestibular nerves, and meningiomas. The UK NF2 Genetic Severity Score (GSS) is useful to predict the progression of the disease from germline NF2 pathogenic variants, which allows the clinical follow-up and the genetic counselling offered to affected families to be optimised.Methods52 Spanish patients were classified using the GSS, and patients’ clinical severity wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Functionality of Merlin-e11 was studied in primary fibroblasts harbouring a heterozygous truncating variant in exon 11: one from an adult patient (Patient_ES11_1) and another from a paediatric patient (Patient_ES11_2) (Table S1). Given the complexity of determining differences in severity in the phenotype from studying the signalling pathways in which Merlin is involved [29], physiological read outs were assessed. Due to the role of Merlin in cytoskeletal organization [38,39], Merlin-e11’s functional activity was first tested through actin immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functionality of Merlin-e11 was studied in primary fibroblasts harbouring a heterozygous truncating variant in exon 11: one from an adult patient (Patient_ES11_1) and another from a paediatric patient (Patient_ES11_2) (Table S1). Given the complexity of determining differences in severity in the phenotype from studying the signalling pathways in which Merlin is involved [29], physiological read outs were assessed. Due to the role of Merlin in cytoskeletal organization [38,39], Merlin-e11’s functional activity was first tested through actin immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The genotype-phenotype correlation of NF2 has long been studied [22][23][24][25][26][27][28][29][30]. For NF2, it is well reported that nonsense variants and large deletions, which account for around 30% of cases, are associated with severe manifestations of the disease, whereas missense, or in-frame variants present a milder form of NF2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic testing of blood, or tissue when available, was performed using a custom NGS Panel (I2HCP), which comprises 135 genes associated with cancer predisposition syndromes and RASopathies, 23 as described by Catasus et al 7 Patients were grouped into 6 classes using the FGSS, which predicts clinical phenotype based on the type of mutation detected, ranging from class 1 (less severe) to class 6 (most severe) (Table S1). Patients were also grouped according to phenotype severity scores calculated using well-known prognostic markers 24,25 at the time of evaluation, as described by Catasus et al 7 Phenotype severity was classified into 4 categories, where group 1 represented the most severe form of disease and group 4 the less severe (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…Further disease‐specific guidelines are currently in development through ClinGen and other curation networks, which incorporate additional disease‐associated features into variant classification; for example, loss of heterozygosity (LOH) and retention of a missense variant in a tumor would be informative for NF2 variant classification. Recently proposed improvements in NF2 genetic severity scores suggest incorporation of merlin functional assays conducted in patient fibroblasts (Catasús et al, 2021), this evidence would be similarly valuable for NF2 variant interpretation.…”
Section: Introductionmentioning
confidence: 99%